Sociology for music teachers practical applications - Froehlich, Hildegard C.; Smith, Gareth Dylan (New York Routledge, 2017)
Sociology for Music Teachers: Practical Applications, Second Edition, outlines the basic concepts relevant to understanding music teaching and learning from a sociological perspective. It demonstrates the relationship of music to education, schooling and society, and examines the consequences for making instructional choices in teaching methods and repertoire selection. The authors look at major theories and concepts relevant to music education, texts in the sociology of music, and thoughts of selected ethnomusicologists and sociologists. The new edition takes a more global approach than was the case in the first edition and includes the application of sociological theory to contexts beyond the classroom.
Why sociology for music teachers? -- The musician and teacher in you: a matter of multiple identites -- Music learning and teaching of socially situated acts -- Teaching as work -- Music in social theories: voices from ethnomusicology, music sociology, cultural theory, and music education -- Sociology of education: social constructs with relevance for music teachers -- The music teacher as value educator -- The sociologically savvy music educator.
Includes bibliographical references and index.
Keywords: Music -- Instruction and study -- Social aspects; MusicxSocial aspects; Educational sociology